2016
DOI: 10.1038/ncomms13241
|View full text |Cite
|
Sign up to set email alerts
|

Robust homology-directed repair within mouse mammary tissue is not specifically affected by Brca2 mutation

Abstract: The mammary gland undergoes significant proliferative stages after birth, but little is known about how the developmental changes impact DNA double-strand break (DSB) repair. Mutations in multiple genes involved in homology-directed repair (HDR), considered a particularly accurate pathway for repairing DSBs, are linked to breast cancer susceptibility, including BRCA2. Using reporter mice that express an inducible endonuclease, we find that HDR is particularly robust in mammary tissue during puberty and pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…One possibility is that breast and ovarian cells are more reliant on HDR than other tissues. This hypothesis was supported by recent in vivo observations of particularly robust HDR activity in proliferative mammary cells compared to other proliferative tissues (Kass et al 2016a). Despite more robust HDR overall, all tissues examined in this study show a similar reliance on BRCA2 for repair of a particular lesion, consistent with BRCA2 having a general role in HDR.…”
Section: Tissue Tropism Of Brca-mutated Cancers and Cell Of Originsupporting
confidence: 66%
“…One possibility is that breast and ovarian cells are more reliant on HDR than other tissues. This hypothesis was supported by recent in vivo observations of particularly robust HDR activity in proliferative mammary cells compared to other proliferative tissues (Kass et al 2016a). Despite more robust HDR overall, all tissues examined in this study show a similar reliance on BRCA2 for repair of a particular lesion, consistent with BRCA2 having a general role in HDR.…”
Section: Tissue Tropism Of Brca-mutated Cancers and Cell Of Originsupporting
confidence: 66%
“…We further quantified HDR in primary ear fibroblasts from Sws1 -/and Swsap1 -/mice containing the DR-GFP reporter 24 and found that HDR levels are similar to controls, as measured directly by the fraction of GFP positive cells or taking into account total I-SceI site-loss ( Supplementary Fig. 5b).…”
Section: Hdr In Mitotic Cells Does Not Require Efficient Rad51 Focusmentioning
confidence: 92%
“…The percent GFP + cells were analyzed 48 h later by flow cytometry. Site-loss were determined using the previously described protocol24 .All mouse ES cell lines were cultured in DMEM-HG medium supplemented with 12.5% stem cell grade FBS (Gemini), 1X Pen-Strep, 1X MEM/NEAA, 1X L-Gln, 833 U/ml LIF (Gemini Cat # 400-495), and 0.1 mM β-mercaptoethanol. Culture dishes were pre-coated with 0.1% gelatin.…”
mentioning
confidence: 99%
“…Brca2 Δ27/Δ27 mice 36 causes an HR defect in somatic cells 37 , there is little discernible effect on RAD51 and DMC1 foci in early meiotic cells and cells progress to later prophase I stages ( Fig. 5a-g).…”
Section: Although Expression Of Brca2 Lacking the C-terminal Domain Inmentioning
confidence: 99%